(untitled) (Journal of Scientific Research, 2016)
The worldwide rising incidence of cardiovascular diseases and the associated risk factors could be country or area specific. A case control study identifying important risk factors of myocardial infarction (MI) prevailing in the northern region of Bangladesh, was conducted in two major northern region hospitals, Rajshahi and Rangpur Medical College for a period of 6 months. Majority of the cases (66%) and controls (56%) were in the age range of 41 60 years. The proportion of male, married and urban residents were predominant in both the case and control group. The highest percentage of patients with MI were involved in business comparatively patients without MI. Clinical symptoms like chest pain, epigastric pain, breathlessness, dizziness and fatigue were observed to be somewhat higher in cases compared to controls. The logistic regression analysis showed that smoking habit, smokeless tobacco consumption, sedentary lifestyle and dyslipidemia were found independent predictors of MI in northern district patients with odds ratio (OR) (95% confidence interval) being 3.1 (1.2 to 3.7), 2.5 (1.0 to 3.5), 2.0 (1.1 to 3.6) and 2.3 (1.3 to 4.1), respectively.